Influence of Chemistry and Misfit Dislocation Structure on Dopant Segregation at Complex Oxide Heterointerfaces. Issue 1 (24th September 2018) - Dholabhai, Pratik P.; Martinez, Enrique; Uberuaga, Blas P.
Abstract: Complex oxide heterostructures and thin films have emerged as promising candidates for diverse applications. Lattice mismatch between the two oxides lead to the formation of misfit dislocations, which influence vital material features. Trivalent dopant segregation to misfit dislocations at semi‐coherent oxide heterointerfaces, while not well understood, is anticipated to impact interface‐governed properties. Here, atomistic simulations elucidating the influence of misfit dislocations on dopant segregation at SrTiO3 /MgO heterointerfaces are reported. SrO‐ and TiO2 ‐terminated interfaces that have differing misfit dislocation structure were considered for trivalent dopants segregation. At SrO‐terminated interface, dopants tend to segregate toward but not precisely to the heterointerface, whereas at TiO2 ‐terminated interface, dopants exhibit a thermodynamic preference to accumulate at the heterointerface. Most favorable segregation sites at SrO‐terminated interface are located within the coherent terrace, whereas those at TiO2 ‐terminated interface are at misfit dislocation intersections. Atomic layer chemistry and the resulting misfit dislocation structure at the heterointerface, along with concomitant strain at the heterointerface due to mismatched dopants, play a critical role in influencing the observed trends for dopant segregation. Overall, the present results offer a fundamental atomic scale perspective of dopant behavior at semi‐coherent complex oxide heterointerfaces and the interplay between dopant chemistry, interface chemistry, and misfit dislocation structure. Abstract : Stoichiometry of the interface atomic layer and concomitant strain at the heterointerface play an important role in dopant segregation to misfit dislocations at semi‐coherent SrTiO3 /MgO heterointerfaces. This work offers a fundamental atomic‐scale perspective of the interplay between dopants, interface chemistry, and misfit dislocation structure.